Mobile App for the Payment of Electronic Tickets Using NFC Technology in the Public Transport System in Lima Metropolitana - Dávila, Fabricio (2024)
The current payment system for public transport on buses in Lima, Peru, is inefficient because it affects the passenger and the service provider in their economy and satisfaction, in addition to not taking advantage of mobile devices and Near-Field Communication (NFC) technology. The contactless ticket payments with NFC has been used in Sweden, Spain, Portugal, Turkey and Chile. The information on mobile payment systems for urban transport, their safety, passenger satisfaction, and payment fares was reviewed. This study proposed two hypotheses to verify that the mobile app improves the quality of service of public transport on buses. For this, the processes and architectures of the app were modeled. Once these were defined, the Android Studio platform was used to implement the native mobile app called My LineCard for the payment of tickets with mobile devices that have NFC technology. The validation was carried out with passengers to evaluate their experience and the usability of the app with a survey. The study concluded that this payment system is more efficient in terms of speed and security thanks to the use of the standardized fare. Finally, the best satisfaction of users for their experience with the app by having control of their payments was highlighted, as well as the ease of installing and using it on the buses.